Phyllosphere mycobiome in two Lycopodiaceae plant species: unraveling potential HupA-producing fungi and fungal interactions - Lin, Liqun; Li, Cheng; Chang, Chiung-Chih; Du, Ran; Ji, Jiaojiao; Kuo, Li-Yaung; Chen, Ko-Hsuan (Frontiers in Plant Science, 2025)
Huperzine A (HupA), a lycopodium alkaloid with therapeutic potential for neurodegenerative diseases such as Alzheimer’s disease, is found exclusively in some species of the Huperzioideae subfamily of Lycopodiaceae. Fungi associated with Huperzioideae species are potential contributors to HupA biosynthesis, offering promising prospects for HupA production. Despite its medical significance, limited knowledge of fungal diversity in lycophytes and the variability of HupA production in fungal strains have impeded the discovery and applications of HupA-producing fungi. Here, we investigated HupA concentrations and the mycobiome across various tissues of two Lycopodiaceae species, Huperzia asiatica (a HupA producer) and Diphasiastrum complanatum (a non-HupA producer). We aim to unveil the distribution of potential HupA-producing fungi in different plant tissues and elucidate fungal interactions within the mycobiome, aiming to uncover the role of HupA-producing fungi and pinpoint their potential fungal facilitators. Among the tissues, H. asiatica exhibited the highest HupA concentration in apical shoots (360.27 μg/g fresh weight) whereas D. complanatum showed no HupA presence in any tissue. We obtained 441 amplicon sequence variants (ASVs) from H. asiatica and 497 ASVs from D. complanatum. The fungal communities in bulbils and apical shoots of H. asiatica were low in diversity and dominated by Sordariomycetes, a fungal class harboring the majority of reported HupA-producing fungi. Integrating bioinformatics with published experimental reports, we identified 27 potential HupA-producing fungal ASVs, primarily in H. asiatica, with 12 ASVs identified as hubs in the fungal interaction network, underscoring their pivotal roles in mycobiome stability. Members of certain fungal genera, such as Penicillium, Trichoderma, Dioszegia, Exobasidium, Lycoperdon, and Cladosporium, exhibited strong connections with the potential HupA producers in H. asiatica’s network rather than in D. complanatum’s. This study advances our knowledge of fungal diversity in Lycopodiaceae and provides insights into the search for potential HupA-producing fungi and fungal facilitators. It highlights the importance of exploring young tissues and emphasizes the ecological interactions that may promote the fungi-mediated production of complex bioactive compounds, offering new directions for research in fungal ecology and secondary metabolite production.